Virtual Laboratory to Improve Students’ Problem-Solving Skills on Electricity Concept (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
The purpose of this study is to examine the effect of the use of virtual labs on problem-solving ability of students to the concept of electricity. The subjects were students of physics education at Mataram University. Students were divided into two groups: experimental and control group. The research instrument used was in the form of problem-solving ability tests on electricity concept. The tests employed the form of essay that represent concepts about electricity being studied. The results showed the effect of the use of virtual labs on problem-solving ability of students to the concept of electricity. It can be seen from the different improvement of problem-solving ability in both groups. Problem-solving ability of experimental group is higher than the control group. From the analysis of these problem-solving steps, it can be seen that general students in both classes have the same ability to identify problems and define goals. In the next step, the different improvement in problem-solving skills in the two classes is significant. Experimental class’ students have a higher ability to plan and implement problem-solving solutions than those of control class.